The Impact of Socioeconomic Factors on Access to Health Services in Turkey: A Logit Analysis - Orhan Çoban; Ayşe Çoban; Emel Mirza (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
This study aims to determine the causes of inequalities in health and to analyze which socio-economic factors are effective on access to health services, by examining the Turkish case. In the analysis, The Turkey Health Survey 2012 micro data from TurkStat and Binary Logistic Regression Method were used. According to the analysis, it is determined that individuals who have lower education and income level are more likely to state poor health status. Also, it is observed that lower education and income level also means lower likelihood of accessing health care and this poses a significant problem against equity. However, income level becomes insignificant on access to healthcare with the sample of individuals stating poor health, probably as a result of increased health insurance coverage by the General Health Insurance Reform.